Monitoring of Total Petroleum hydrocarbons (TPHs) in the sediments of some local regions of southern Iraq - Al-Gizzi, Israa A.; Qzar , Inaam A.; Al-Kinany, Sudad A. (Mesopotamian Journal of Marine Sciences, 2021)
Petroleum hydrocarbons are pollutants with a wide range of dangerous organic chemicals, which have received a considerable attention because they are widely distributed in the environment, many of which have a mutated potential, cause genetic toxicity and carcinogenic effects on natural ecosystems. Spatiotemporal variations of total petroleum hydrocarbons (TPHs) in the sediments of some regions of southern Iraq were measured during 2019, the highest concentration were 14.94 µg/g in Al-Burqa at Al-Hammar marsh, and the lowest was 2.05 µg/g in Al-Sadda station in the East of Al-Hammar marsh too. These results were compared with previous studies since 1982 in the same region, these studies were calculated to estimate a bulk value for each study. The results of the present study showed that TPHs concentration in water and sediments at Al-Hammar marsh, Al-Chibayesh marsh and Shatt Al-Arab river were within the permissible limits and there were no significant differences spatially and temporally in the study area. So we can conclude that there is no real total petroleum hydrocarbons pollution in these specific water bodies southern Iraq since 1982.